(untitled) (Fiep Bulletin - online, 2016)
Exceed expectations to retain customers and become professional, an increasing challenge to martial arts academies. Introduction: In an increasingly globalized environment, where each individual has specific needs, and the martial art academies increasingly become standardized, the challenge will be how to differentiate and gain advantage, to offer quality of life and innovation to customers. Objective: To identify the factors causing the evasion of customers, levels of managerial preparation of teachers and proprietors of academies and provide solutions for threat identification and development of management improvements. Methodology: The sample consisted of 27 teachers from different martial arts academies, who responded individually to the questionnaire containing 67 questions related to nine subjects, expressed as services, promoting services, outreach / promotion, social identity, professionalism, physical structure, management, compliance and sociability, in order to assess the quality of services offered by the public academies, totaling a database with 1809 records. Results: the results indicated a low level of preparedness of both professionals and managers, poor infrastructure as well as low innovation in the sector. Conclusion: It was determined that the high evasion is given by the technical inability of the administrators and teachers in improving their facilities and make the constantly dynamic activity.